Pharmacodynamic Monitoring of RO5459072, a Small Molecule Inhibitor of Cathepsin S - Theron, Michel; Bentley, Darren; Nagel, Sandra; Manchester, Marianne; Gerg, Michael; Schindler, Thomas; Silva, Ana; Ecabert, Barbara; Teixeira, Priscila; Perret, Camille; Reis, Bernhard (Frontiers in Immunology, 2017)
MHC class II-restricted antigen priming of CD4+ T cells is both involved in adaptive immune responses and the pathogenesis of autoimmune diseases. Degradation of invariant chain Ii, a protein that prevents premature peptide loading, is a prerequisite for nascent MHCII-peptide complex formation. A key proteolytic step in this process is mediated by Cathepsin S. Inhibition of this cysteine protease is known to result in the intracellular accumulation of Lip10 in B cells. Here we describe the development and application of a neoepitope based flow cytometry assay measuring accumulation of Lip10. This novel method enabled the investigation of Cathepsin S dependent MHCII maturation in professional antigen presenting cell subsets. Inhibition of Cathepsin S by a specific inhibitor, RO5459072, in human PBMC ex vivo resulted in accumulation of Lip10 in B-cells and myeloid Dendritic cells, but not in plasmacytoid Dendritic cells and only to a minor degree in monocytes. We qualified Lip10 as a pharmacodynamic biomarker by showing the Cathepsin S inhibitor dependent accumulation of Lip10 in vivo in Cynomolgus monkeys treated with RO5459072. Finally, dosing of RO5459072 in a first-in-human clinical study (ClinicalTrials.gov identifier: NCT02295332) exhibited a dose-dependent increase in Lip10, confirming target engagement and demonstrating desired pharmacologic inhibition in vivo. The degree of Cathepsin S antagonist induced maximum Lip10 accumulation in antigen presenting cells varied significantly between individuals both in vitro and in vivo. This finding has not been reported previously using alternative, less sensitive methods and demands further investigation as to the potential of this biomarker to predict response to treatment. These results will help guide subsequent clinical studies investigating the pharmacokinetic and pharmacodynamic relationship of Cathepsin S inhibitor RO5459072 after multiple dosing.